2011
DOI: 10.1016/j.ejcts.2011.02.041
|View full text |Cite
|
Sign up to set email alerts
|

Positron emission tomography for predicting recurrence in stage I lung adenocarcinoma: standardized uptake value corrected by mean liver standardized uptake value

Abstract: The SUV index is a significantly predictive and reproducible factor for recurrence in pathological stage I lung cancers. Patients with an SUV index <1.0 were more likely to have a good prognosis. Additional multi-institutional studies are needed to confirm these study results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 24 publications
1
27
0
Order By: Relevance
“…We have demonstrated the usefulness of the SUV index (ratio of tumor SUV max to liver SUV mean ) in previous reports. 12,13) This study found that an SUV index <1.2 had a 97.8% NPV and clearly differentiated malignant from benign pulmonary nodules. A major limitation of our study is that PET is less sensitive for nodules <8 mm.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…We have demonstrated the usefulness of the SUV index (ratio of tumor SUV max to liver SUV mean ) in previous reports. 12,13) This study found that an SUV index <1.2 had a 97.8% NPV and clearly differentiated malignant from benign pulmonary nodules. A major limitation of our study is that PET is less sensitive for nodules <8 mm.…”
Section: Discussionmentioning
confidence: 92%
“…For this study, the data of patients who underwent thoracic surgery was prospectively collected, and entered into a database that had been established to investigate patients undergoing thoracic surgery at our institution. The following data were collected: age, gender, smoking status, comorbidities, maximum tumor size, imaging characteristics of the nodules, chest CT findings, SUV index (ratio of SUV max of the tumor to SUV mean of the right lobe of the liver), 12,13) surgical procedure, and findings. Regarding patients with a metastatic pulmonary nodule, the diseasefree interval (DFI), defined as the date of first treatment to the appearance of lung metastasis, was recorded.…”
Section: Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…We speculate that differences in cutoff values of SUVmax will occur even in homogeneous populations because of differences in scanning devices and methods among institutions. Shiono, et al 10) used a corrected SUV, which they termed the SUV index, and calculated this as the ratio of tumor SUV (max) to liver SUV (mean). They found that the SUV index was reproducible and was a significant predictor of recurrence Months of pathological stage I NSCLC.…”
Section: Discussionmentioning
confidence: 99%